Social Reflection Presented in the Novel Kaen Mai Hom by King Chat - phongsaphang, Apinya; Nunphooban, Suratadchanukoon; Sukkhong, Sarisa (Mahachula Academic Journal, 2025)
The novel Kaen Mai Hom narrates the life of the protagonist, a Thai woman of Chinese descent named Siu Heung, who migrated from China to Thailand with her parents during her childhood in the aftermath of the Second World War. Her life encompasses experiences of joy and suffering across different eras, particularly in her roles as a wife and mother. Her personal journey reflects broader sociocultural and economic transformations over time. Thus, Thus, this academic article aims to purpose on Social Reflection Presented in the Novel Kaen Mai Hom, a novel written under the pen name King Chat and published in ๒๐๒๓. The analysis and interpretation of the narrative are grounded in the social reflection theory. The Analysis of novel Kaan Mai Hom reflects seven aspects of society: (1) the reflection of general livelihood, such as; lifestyle related to occupations and making a living, lifestyle related to urban and rural environments, and Lifestyle related to transportation; (2) the reflection on family, such as portrayals of nuclear and extended families and problems in family relationships; (3) the reflection on beliefs, such as religious beliefs, beliefs about death, beliefs in astrology, and beliefs about birth and rebirth; (4) the reflection on values, such as values regarding education, values concerning child preference and gender selection, values related to marriage, values in naming businesses, and values and stigma around widows; (5) the reflection on culture, including important cultural festivals, funeral customs, wedding traditions, banquet culture, customs of monetary gifts, kinship naming conventions, and practices of familial respect and hierarchy; (6) the reflection on Economy, Politics, and Governance, such as economic conditions during the Tom Yam Kung crisis, the reflections on World War II events, and the reflections on the October 6, 19 76 massacre; and (7) the reflection on education in society, such as the educated vs. the underprivileged in education and the comparisons between government and private schooling,.The social reflection evident in the novel Kaen Mai Hom by Kingchat is portrayed through the life story of Siu Heang, from childhood until the end of her days. As the saying goes, "Literature is like a mirror that reflects the realities of society and humanity."